ANALYSIS OF INDONESIA’S MARKET POSITION IN REFINED PALM OIL (RPO) MARKET IN IMPORTER COUNTRIES - Aulia, Risnayanti Ulfa; Harianto, Harianto; Novianti, Tanti (Jurnal Penelitian Kelapa Sawit, 2019)
Indonesia is one of the largest producer and exporter of palm oil in the world. The downstream policy of palm oil causes Indonesia’s export more derivative products in form of Refined Palm Oil (RPO) than Crude Palm Oil (CPO) . Indonesia also faced competition with Malaysia as an RPO’s exporter in several importing countries such as China, India, Russia and the United States. This study aims to analyze the competition between Indonesia and Malaysia in several RPO’s importing countries. The model used Almost Ideal Demand System (AIDS). Based on the results, Indonesia’s RPO prices are more elastic in the India and US markets, while Malaysia’s RPO prices are more elastic in Russian market. Although Indonesia’s and Malaysia’s RPO substitute each other, but Indonesia’s position is more profitable than Malaysia if the importing countries increase spending on RPO imports because it will increase the import’s shares from Indonesia.